The pathogenesis of Helicobacter pylori associated diseases in Kurdistan region, Iraq - Hussein, Nawfal Rasheed (2009)
Helicobacter pylori is regarded as the most important risk factor for peptic ulcer disease and gastric cancer. In Kurdistan region, northern Iraq, gastric cancer is rare (5/100,000). To investigate some possible reasons for this, the prevalence of H. pylori infection, gastric mucosal histopathological changes in H. pylori infected subjects, and virulence factor genotypes (especially dupA) of colonising strains were studied. The immune response to H. pylori infection, focusing on genes associated with T-helper (Th) and regulatory T-cell (Treg) cells, was also investigated.